2019
DOI: 10.1111/fwb.13278
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient management and structural shifts in fish assemblages: Lessons learned from an Area of Concern in Lake Ontario

Abstract: While total phosphorus (TP) is a critical determinant of freshwater ecosystem productivity, multiple stressors can induce shifts in energy pathways, with profound implications for ecosystem and fishery restoration. The Bay of Quinte (Lake Ontario, Canada) is a Great Lakes nearshore ecosystem that has been historically subjected to a variety of environmental perturbations: cultural eutrophication, low dissolved oxygen, reduced fisheries, climatic extremes, phosphorus (P) abatement, and aquatic invasive species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…A number of studies have documented that the proportions of zooplanktivores and omnivores were positively related to nutrients, whereas the percentage of piscivores decreased markedly with lake productivity [24,27,65]. For our subtropical lakes, we also found that the proportion of all zooplanktivores (zooplanktivores + omniplanktivores) increased significantly with lake productivity, while the proportion of piscivorous fish decreased.…”
Section: Discussionsupporting
confidence: 67%
“…A number of studies have documented that the proportions of zooplanktivores and omnivores were positively related to nutrients, whereas the percentage of piscivores decreased markedly with lake productivity [24,27,65]. For our subtropical lakes, we also found that the proportion of all zooplanktivores (zooplanktivores + omniplanktivores) increased significantly with lake productivity, while the proportion of piscivorous fish decreased.…”
Section: Discussionsupporting
confidence: 67%
“…Our observations are consistent with the "nearshore phosphorus shunt" (Hecky et al 2004), which posits that dreissenid mussel filtering would intercept additional nutrients as plankton from offshore areas, reduce food availability for pelagic fishes, sequester nutrients in nearshore benthos, and clarify the water column, fostering additional vegetative growth. Such changes, commonly referred to as "benthification", have resulted in less energy available at higher trophic levels and reductions in many fish populations in the Great Lakes (Hossain et al 2019). The near disappearance of pelagic forage fish species from trawl and gill-net collections in both bays in the early 2000s (and their decline in Walleye diets) coincide with the timing of quagga mussel colonization of northern Green Bay and steep declines in pelagic prey fish abundance in the main basin of Lake Michigan (Madenjian et al 2015).…”
Section: Fish Community Changesmentioning
confidence: 99%
“…The influence of eutrophication on populations varies among species, with some species benefitting while others are disfavoured, altering the species composition of communities ( Hossain et al, 2019 ; Jeppesen et al, 2005 ; Mehner et al, 2005 ). The threespine stickleback appears to be a winner in profiting from both increased offspring production ( Candolin, Nieminen & Nyman, 2014 ) and reduced predation pressure ( Bergström et al, 2015 ), possibly at the expense of other species ( Candolin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%